The status of striped bass, Morone saxatilis, as a commercially ready species for U.S. marine aquaculture. Issue 3 (24th May 2021) - Andersen, Linnea K.; Abernathy, Jason; Berlinsky, David L.; Bolton, Greg; Booker, Matthew M.; Borski, Russell J.; Brown, Travis; Cerino, David; Ciaramella, Michael; Clark, Robert W.; Frinsko, Michael O.; Fuller, S. Adam; et al.
Abstract: Striped bass, Morone saxatilis, is an anadromous fish native to the North American Atlantic Coast and is well recognized as one of the most important and highly regarded recreational fisheries in the United States. Decades of research have been conducted on striped bass and its hybrid (striped bass × white bass Morone chrysops ) and culture methods have been established, particularly for the hybrid striped bass, the fourth largest finfish aquaculture industry in the United States (US $50 million). Domesticated striped bass have been developed since the 1990s and broodstock are available from the government for commercial fry production using novel hormone‐free methods along with traditional hormone‐induced tank and strip spawning. No commercial‐scale intensive larval rearing technologies have been developed at present and current fingerling production is conducted in fertilized freshwater ponds. Larval diets have not been successfully used as first feeds; however, they have been used for weaning from live feeds prior to metamorphosis. Striped bass can be grown out in marine (32 ppt) or freshwater (<5 ppt); however, they require high hardness (200+ ppm) and some salinity (8–10 ppt) to offset handling stress. Juveniles must be 1–10 g/fish prior to stocking into marine water. Commercially available fingerling, growout, and broodstock feeds are available from several vendors. Striped bass may reach 1.36 kg/fish in recirculating aquaculture by 18 months and as much as 2.27 kg/fish by 24 months. Farm gate value of striped bass has not been determined, although seasonally available wild‐harvested striped bass are valued at about US $6.50 to US $10.14 per kg and cultured hybrid striped bass are valued at about US $8.45 to US $9.25 per kg whole; the farm gate value for cultured striped bass may be as much as US $10.00 or more per kg depending on demand and market. The ideal market size is between 1.36 and 2.72 kg/fish, which is considerably larger than the traditional 0.68 to 0.90 kg/fish for the hybrid striped bass market.